THE ROLE OF INFORMATION SYSTEMS IN BUSINESS PROCESS ANALYSIS - Srajidinova Nodira Shavkatovna (Ecominds Press, 2025)
This article examines the significance of information systems in the analysis of business processes. The study highlights how modern technologies and information systems help organizations improve efficiency, optimize decision-making, and ensure effective management. The implementation of information systems enables companies to automate routine operations, increase productivity, and achieve competitive advantages in a rapidly changing business environment.
Keywords: Information system, business process, analysis, management, optimization, technology.